Day–Night Synergy Between Built Environment and Thermal Comfort and Its Impact on Pedestrian Street Vitality: Beijing–Chengdu Comparison - Jinjiang Zhang; Xuan Li; Haitao Lian; Haozhe Li; Junhan Zhang (Buildings, 2025)
With the acceleration of urbanization, existing studies have primarily focused on the influence of either built environment factors or thermal comfort on street vitality, while their synergistic effects remain underexplored. This study selects four pedestrian commercial streets in Beijing and Chengdu for dual validation to reveal the varying impacts of built environment elements on street vitality under different climatic conditions and to uncover the diurnal dynamic effects. The key findings include the following: (1) the shop width (optimal between 8 and 14 m) and the number of items of street furniture are the core drivers of vitality across time and space; (2) although the visibility of greenery is often recommended to boost vitality, its influence is nonlinear and closely tied to thermal comfort; (3) thermal comfort and street width dynamically affect the spatiotemporal variations in vitality; and (4) daytime vitality is mainly driven by spatial comfort related to commercial density, furniture, and thermal comfort, while nighttime vitality relies more on the synergy between street width and shop transparency. This study aims to support differentiated street design across climates, enhancing both economic vitality and sustainable urban development.